2017
DOI: 10.9758/cpn.2017.15.2.177
|View full text |Cite
|
Sign up to set email alerts
|

Dose Trends of Aripiprazole from 2004 to 2014 in Psychiatric Inpatients in Korea

Abstract: ObjectiveAlthough aripiprazole has been widely used to treat various psychiatric disorders, little is known about the adequate dosage for Asian patients in clinical practice. Hence, we evaluated the initial and maximum doses of aripiprazole from 2004 to 2014 to estimate the appropriate dosage for Korean psychiatric inpatients in clinical practice.MethodsIn this retrospective study, we reviewed the medical records of patients who were hospitalized in five university hospitals in Korea from March 2004 to Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…However, another meta-analysis suggested that ARP monotherapy could be effective for treating of acute depression because combined data from two negative studies revealed a significant effect 52,53). Additionally, in Korea, the proportion of patients with bipolar depression prescribed with ARI was increased from 1.4% (2004–2006) to 8.5% (2011–2014), but the mean initial and maximum dose was 15 and 30 mg/day respectively in 2004–2006 and 6.3 and 16.8 mg/day respectively in 2011 to 2014 54). The high preference and use of ARP for treating bipolar depression in Korea could be based on some evidence that supports the efficacy of ARP for bipolar depression.…”
Section: Discussionmentioning
confidence: 99%
“…However, another meta-analysis suggested that ARP monotherapy could be effective for treating of acute depression because combined data from two negative studies revealed a significant effect 52,53). Additionally, in Korea, the proportion of patients with bipolar depression prescribed with ARI was increased from 1.4% (2004–2006) to 8.5% (2011–2014), but the mean initial and maximum dose was 15 and 30 mg/day respectively in 2004–2006 and 6.3 and 16.8 mg/day respectively in 2011 to 2014 54). The high preference and use of ARP for treating bipolar depression in Korea could be based on some evidence that supports the efficacy of ARP for bipolar depression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ARI has been increasingly prescribed for patients with bipolar depression at a continuously decreasing dosage. In a retrospective study with psychiatric in-patients, 42) the proportion of patients with bipolar depression who were prescribed ARI increased from 1.4% (2004–2006) to 8.5% (2011–2014), but the prescribed mean initial and maximum dose was 15 and 30 mg/day, respectively in 2004 to 2006 and was 6.3 and 16.8 mg/day, respectively in 2011 to 2014. The preference for, and high usage of, ARI for treating bipolar depression in Korea could be based on evidence supporting the efficacy of ARI for treating bipolar depression or result from the unavailability of certain medications including lurasidone, which was recommended as the first-line in other evidence-based guidelines in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Another meta-analysis suggested that ARP monotherapy could be effective for treatment of acute depression because combined data from two negative studies revealed a significant effect [ 55 , 63 ]. Reportedly in Korea, the proportion of patients with bipolar depression prescribed with ARP increased from 1.4% (2004−2006) to 8.5% (2011−2014), but the mean initial and maximum dose was 15 mg/day and 30 mg/day respec-tively in 2004−2006 and 6.3 mg/day and 16.8 mg/day respectively in 2011−2014 [ 64 ]. The high preference for, and use of ARP for treating bipolar depression in Korea could be based on some evidence that supports the efficacy of ARP for bipolar depression.…”
Section: Discussionmentioning
confidence: 99%